The development of a leaching procedure to determine the effectiveness of immobilising Nickel as a heavy metal in solid wastes - Jansen van Rensburg, Aletta Elizabeth (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1997.